COVID-19, human rights and the State in the Management of the Pandemic - Sánchez Díaz, María Fernanda (Universidad Nacional del Litoral, 2021)
Human Rights are already taken for granted by many people. We have become accustomed to seeing them in Constitutional texts and we think that the Authority will respect them without any problem and will do everything in their power to make them effective. Notwithstanding the foregoing, the pandemic generated by the coronavirus demonstrated how difficult it is as a government to make decision that may affect the exercise of some human rights, but this decision is to safeguard a more important right such as life.